GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2017)
A dataset containing 3458433 species occurrences available in GBIF matching the query: Geometry: POLYGON((-180 -90, -180 -45, 180 -45, 180 -90, -180 -90)). The dataset includes 3458433 records from 1495 constituent datasets: 12 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 8 records from Naturalis Biodiversity Center (NL) - Crustacea. 1217 records from The molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 4092 records from Ross Sea Biodiversity Survey 2004 (BioRoss). 102 records from Plan de vertebrados de la Patagonia. 10139 records from International Barcode of Life project (iBOL). 3925 records from Free-living Nematodes from Patagonia coastal lagoons (Chubut, Santa Cruz, Argentina).. 2 records from JOI - Herbário Joinvillea. 10030 records from Free-living marine Nematodes from San Julián bay (Santa Cruz, Argentine), 2009.. 365 records from A global database for the distributions of crop wild relatives. 19 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 8478 records from International Polar Year and Census of Antarctic Marine Life Ross Sea voyage (TAN0802) biodiversity data. 1 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 1 records from HUEM - Herbário da Universidade Estadual de Maringá. 8 records from Kirkegaardia (Polychaeta, Cirratulidae), new name for Monticellina Laubier, preoccupied in the Rhabdocoela, together with new records and descriptions of eight previously known and sixteen new species from the Atlantic, Pacific, and Southern Oceans. 15 records from HUFU - Herbarium Uberlandense. 16 records from Phanerogamic Botanical Collections (S). 143 records from Mollusca collection of National Museum of Nature and Science. 90 records from MVZ Herp Collection (Arctos). 8 records from University of Vienna, Institute for Botany - Herbarium WU. 5 records from UFG - Herbário da Universidade Federal de Goiás. 55 records from Colección de Entomología - Diptera - Ceratopogonidae. 304 records from Succession of benthic hard-bottom communities abundance at station Errina2012_IS_solar2. 1025 records from (Appendix 2) Absolute abundance of nannofossils in ODP Hole 183-1135A. 20 records from LSUM Bernard Lowy Mycological Herbarium at Louisiana State University - Fungi. 116 records from MVZ Mammal Collection (Arctos). 346 records from Australian National Wildlife Collection provider for OZCAM. 1 records from Reuniting males and females: redescriptions of Nuisiana arboris (Marples 1959) and Cambridgea reinga Forster & Wilton 1973 (Araneae: Desidae, Stiphidiidae). 4316 records from PolE At Sea Observations of Birds and Marine Mammals during PS 81 (ANT-XXIX/4). 2 records from Coleção de Aves do Museu Nacional / UFRJ. 1 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 6 records from LACM Entomology Collection. 779 records from Biota occurrence data from plankton surveys around New Zealand. 21 records from Bryophyte herbarium, Tromsø Museum. 9 records from IAC - Herbário do Instituto Agronômico de Campinas. 41 records from Bee Biology and Systematics Laboratory. 5 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 1056 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 23 records from AntWeb. 17 records from (Table 3) Benthic foraminifera in Southwest Indian Ocean surface sediments. 5 records from CAS Entomology (ENT). 88 records from Zoology (Museum of Evolution - Uppsala). 676 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 11 records from PlutoF platform observations. 68 records from Herbarium Senckenbergianum (GLM) - Lichenes. 15 records from Biodiversity Research and Teaching Collections - TCWC Marine Invertebrates. 25 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 5 records from PRECIS. 83 records from Colección de Crustacea del Museo Nacional de Historia Natural de Chile. 638 records from CSIRO Ichthyology provider for OZCAM. 2929 records from Fishbase. 33 records from UTEP Plants (Arctos). 729 records from Occurrence records of southern African aquatic biodiversity. 14 records from SPF - Herbário da Universidade de São Paulo. 1 records from The Neotropical tanyderid Araucoderus gloriosus (Alexander) (Diptera, Tanyderidae), with description of the egg, larva and pupa, redescription of adults, and notes on natural history. 32 records from (Table T1) Dinoflagellate cyst and spore/pollen yield and preservation in ODP Leg 188 sites. 384 records from (Supplement Table) Individual body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 7 records from SANT Herbarium vascular plants collection. 5 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 69 records from KUBI Mammalogy Collection. 266 records from Biological Reference Collections ICM CSIC. 1 records from Colección de Entomología - Arthropoda. 12 records from UFP - Herbário UFP - Geraldo Mariz. 1 records from University of Amsterdam (NL) - Páramo pollen reference collection. 2 records from Cercle des mycologues de Montréal Fungarium (CMMF). 3 records from ICN - Herbário do Instituto de Ciências Naturais. 2 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 287 records from Colección Herpetológica del Museo Nacional de Historia Natural de Chile. 1 records from Herbario Universidad de Antioquia (HUA). 17 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 26 records from Revision of the genera Pareuthria Strebel, 1905, Glypteuthria Strebel, 1905 and Meteuthria Thiele, 1912 (Gastropoda: Buccinulidae) with the description of three new genera and two new species from Southwestern Atlantic waters. 633 records from The avian collection at the Natural History Museum, Oslo, Norway. 76 records from (Fig. 2) Vertical density profiles of meiofauna taxa in surface sediments of Potter Cove, King George Island, Antarctic Peninsula. 190 records from A Distribution and Taxonomic Reference Dataset of Geranium (Geraniaceae) in the New World. 189 records from Lyman Entomological Museum (LEMQ). 331 records from La colección briológica del Herbario Nacional (MEXU). Actualización 2000. 63 records from (Data S1) Palynology of ODP Site 119-739. 30 records from Studies on the Zoarcidae of the southern hemisphere. X. New records from western Antarctica.. 24136 records from IMOS - AusCPR: Phytoplankton Abundance. 83606 records from New Zealand fish and squid distributions from research bottom trawls 1964-2008. 22 records from NCSM Fishes Collection. 113 records from AM: Freshwater Invertebrates (1900-2005). 200 records from (Table T1) Neogene stratigraphy of diatoms, ebridians and endoskeletal dinoflagellates in ODP Hole 183-1138A. 70 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 83 records from Culture Collection of Cryophilic Algae. 50 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 2 records from The Scorpiones collection (RS) of the Muséum national d'Histoire naturelle (MNHN - Paris). 216 records from (Table T1) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1135A. 1 records from UAM Fish Collection (Arctos). 188 records from DMNS Bird Collection (Arctos). 733 records from Antarctic Porifera database from the Spanish benthic expeditions: Bentart, Gebrap and Ciemar. 70 records from The Fish Collection at the Zoologische Staatssammlung München. 16 records from University of Florida Vertebrate Paleontology. 8 records from (Table 1) Trawled distance, Isopoda per 1000 m haul length, expected number of species, evenness, and the Shannon-Wiener index during POLARSTERN cruise ANT-XIX/3 (ANDEEP I). 1 records from Sipuncula collection of National Museum of Nature and Science. 14 records from Museu Paraense Emilio Goeldi Herbarium. 8 records from Coleção de Echinodermata do Museu Nacional - MNRJ-ECHINO. 8 records from (Table 2) Monthly statistics of king penguin (Aptenodytes patagonicus) colony arrivals, Possession Island. 4 records from CESJ - Herbário Leopoldo Krieger. 5 records from OUPR - Herbário "Professor José Badini". 1086 records from Colección Nacional de Aracnología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 8 records from CMC Cincinnati Museum Center Invertebrate Paleontology. 68 records from Field Museum of Natural History (Zoology) Bird Collection. 2 records from Mycology herbarium, Tromsø Museum. 520 records from UAM Mammal Collection (Arctos). 1316 records from IZIKO: Marine Invertebrate Collection (1900-2011). 3 records from Collection des Mollusques (BOUM). 68 records from Reef Life Survey: Global reef fish dataset. 546 records from Colección de Algas del Herbario Nacional, Museo Nacional de Historia Natural de Chile. 9499 records from Museum Victoria provider for OZCAM. 43 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 71 records from (Data S1) Palynology of ODP Site 113-696. 17 records from (Table T4) Calcareous nannofossil abundance of ODP Site 189-1171 sediments. 16 records from (Table V) Distribution of diatoms in samples from Heidemann Valley trench, Antarctica. 11 records from Cowan Tetrapod Collection - Mammals. 626 records from Herbario Nacional de Plantas Celulares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 253 records from MBM - Herbário do Museu Botânico Municipal. 5 records from International Collection of Microorganisms from Plants (ICMP). 7 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 8 records from (Appendix B) Benthic foraminifera in Indian Ocean surface sediments. 50 records from ZUEC-POL - Coleção de Polychaeta do Museu de Zoologia da UNICAMP. 18 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 129 records from (Appendix B) Dinoflagellate cysts in Southeast Pacific Ocean surface sediments. 48 records from (Table T2) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1136A. 107 records from (Appendix 3) Calcareous nannofossils in ODP Hole 113-690B. 3 records from BMSM Bailey-Matthews National Shell Museum. 44 records from HSU Wildlife Mammals. 2873 records from Field Museum of Natural History (Zoology) Mammal Collection. 1 records from MVZ Hildebrand Collection (Arctos). 1 records from Ornithologie ZMK. 67 records from Lund Museum of Zoology (MZLU). 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 494 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 1 records from Vermes ZMK. 10 records from FCAB - Herbário Friburguense. 1 records from Crustacea ZMK. 1719 records from CAS Invertebrate Zoology (IZ). 12 records from Crustacea collection of National Museum of Nature and Science. 319 records from IMOS - AusCPR: Zooplankton Abundance. 111 records from (Table T5) Relative abundance of Eocene plant microfossil taxa of ODP Site 188-1166. 217 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD7. 37 records from Tallinn Botanic Garden. 44 records from (Data S1) Palynology of IODP Hole 318-U1360A. 554 records from Colección de Zoología Invertebrados - Otros invertebrados. 24 records from NCSM Birds Collection. 69 records from UAM Bird Collection (Arctos). 151 records from (Table T1) Biostratigraphy and distribution of Quaternary and Miocene calcareous nannofossils in ODP Site 188-1165. 2493 records from (Table T1) Foraminifer abundance of ODP Hole 188-1165B. 468 records from BirdLife Australia, Birdata. 1665 records from Museum of Comparative Zoology, Harvard University. 33 records from Marine gastropod distribution from patagonian shallow waters. 39 records from Naturalis Biodiversity Center (NL) - Cnidaria. 9399 records from Australia's Virtual Herbarium. 4 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 555 records from (Appendix 1) Abundances of benthic forminifera in ODP Hole 113-689B. 46 records from (Table T2) Stratigraphic distribution of dinoflagellates and pollen/spores by age class, ODP Leg 188 sites. 108 records from Ichthyology Collection - Royal Ontario Museum. 335 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 14 records from CAS Ornithology (ORN). 293352 records from EOD - eBird Observation Dataset. 438 records from Tasmanian Museum and Art Gallery provider for OZCAM. 12610 records from iNaturalist Research-grade Observations. 277 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 13 records from UCBG TAPIR Provider. 177 records from CONN. 41 records from HUCS - Herbário da Universidade de Caxias do Sul. 2 records from Type Collection of the Seto Marine Biological Laboratory, Kyoto University. 1 records from Invertebrate collection of the Seto Marine Biological Laboratory, Kyoto University. 38 records from NYSM Birds. 9 records from Cnidaria Collection of the Seto Marine Biological Laboratory, Kyoto University. 5 records from Recent Invertebrates Specimens. 64 records from Coleção de Polychaeta do Museu Nacional. 1975 records from Invertebrates Collection of the Swedish Museum of Natural History. 14 records from KUBI Ichthyology Tissue Collection. 7842 records from Global Lacustrine Diatoms. 4 records from University of California Museum of Paleontology. 13 records from UCT: Southern African Butterfly Conservation Assessment (1815-2009). 4268 records from Free-living marine Nematodes from Ali, Rada Tilly and El Limite sandy beaches (Chubut, Argentina) 2006.. 24 records from (Tables 1,2) Site characteristics and phenotypic attributes of King Penguins (Aptenodytes patagonicus) on Possession Island. 1 records from HFSL - Herbário Dr. Ary Tupinambá Penna Pinheiro. 49 records from Mammals housed at MHNG, Geneva. 84 records from ALCB - Herbário Alexandre Leal Costa. 28 records from (Table 2) Distribution of the endemic fly (Anatalanta aptera) and the introduced ground beetle (Merizodus soledadinus) on the Kerguelen Islands. 1 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 1 records from Estonian University of Life Sciences. 528 records from CAS Ichthyology (ICH). 162 records from Colección Plantas Vasculares - Herbario del Departamento de Biología, Bioquímica y Farmacia de la Universidad Nacional del Sur. 2519 records from Marine biological observation data from coastal and offshore surveys around New Zealand. 739 records from The Diatom Collection of Franz Josef Weinzierl at the Botanische Staatssammlung München. 9 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 1440 records from (Table 21) Benthic foraminifera in middle Miocene sediments of DSDP Hole 90-594. 29 records from DMNS Mammal Collection (Arctos). 16 records from Fiocruz/COLTRYP - Coleção de Trypanosoma de Mamíferos Silvestres, Domésticos e Vetores. 7 records from (Table T4) Nannofossil counts accross the K/T boundary in ODP Hole 183-1138A. 1429 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 19 records from University of British Columbia Herbarium (UBC) - Lichen Collection. 49 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 1 records from Colección de Entomología - Auchenorrhyncha. 64 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 630 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Cryptogamic National Collection (BAc).. 216 records from (Table 2a) Downcore distribution of live benthic foraminifera of sediment core PS1394-1, Weddell Sea. 140 records from (Table 2b) Downcore distribution of live benthic foraminifera of sediment core PS1394-3, Weddell Sea. 191 records from Seaweeds records from Argentina and Uruguay. 4658 records from Live benthic foraminifera in South Atlantic surface sediments. 28 records from Counts of recycled Pliocene foraminifera of sediment core CRP-1 (App. 1). 1 records from LUSC - Herbário de Lages da Universidade do Estado de Santa Catarina. 248 records from Counts of Quaternary foraminifera of sediment core CRP-1 (App. 1). 181 records from Occurence of monothalamous foraminifera in Admiralty Bay, King George Island, West Antarctica (Table 1, 2). 2 records from Diveboard - Scuba diving citizen science observations. 117 records from Bryophyte herbarium, NTNU University Museum. 1351 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Herpetology National Collection (MACNHe).. 16 records from Illinois Natural History Survey Insect Collection. 751 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Vascular Plants National Collection (BAv).. 2 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 1 records from A revision of the genus Lepidobrya Womersley (Collembola: Entomobryidae) based on morphology and sequence data of the genotype. 4 records from VIC - Herbário da Universidade Federal de Viçosa. 444 records from The Brown University Foraminiferal Data Base (BFD). 52 records from (Table T8) Occurrence of Neogloboquadrina pachyderma in ODP Hole 178-1098C. 4 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/009-6. 5 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/011-3. 9 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/012-4. 6 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 3 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/038-7. 27 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/041-5. 5 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/042-5. 13 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 14 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/045-9. 8 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/046-5. 12 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/048-5. 7 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/049-5. 13 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/061-3. 11 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/088-7. 14 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/090-2. 12 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/091-3. 12 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/092-6. 15 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/107-6. 12 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/108-3. 59 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/424-22. 46 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/427-6. 66 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/508-22. 53 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/509-16. 53 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/511-12. 49 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/514-18. 60 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/543-5. 45 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/544-6. 61 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/546-19. 62 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/553-11. 58 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/570-14. 44 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/580-12. 68 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/587-14. 68 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/593-9. 11 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 55 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/590-1. 24 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 14 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-14. 10 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-17. 16 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 22 records from Polychaeta Orbiniidae from Antarctica, the Southern Ocean, the Abyssal Pacific Ocean, and off South America. 21 records from Colección preservada Jardín Botánico de la Patagonia Extraandina. 569 records from (Appendix A) Planktonic foraminiferal abundances in DSDP Hole 90-594 from the South Chatham Rise, southeastern New Zealand. 40 records from Stable carbon and oxygen isotope ratios of calcareous dinoflagellate cysts and planktic foraminifera from the Campanian/Maastrichtian section of ODP Hole 113-690C in the Weddell Sea (Table 1). 3 records from Dinoflagellate assemblage in surface sediments of the South Atlantic. 931 records from Colección Ictiológica del CENPAT-CONICET. 70 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 14 records from Phytoplankton counted in three surface sediment samples from the South Atlantic at station PS2230-1, PS2367-1 and PS2376-2. 75 records from Abundance of microzooplankton measured on water bottle samples during POLARSTERN cruise ANT-X/6. 1850 records from (Appendix 2) Abundances of benthic forminifera in ODP Hole 113-690B. 1016 records from naturgucker. 19 records from Institut Botanic de Barcelona (IBB-CSIC-ICUB), BC-Lichen. 56 records from (Table T2) Dinoflagellate cyst occurrence in neogene sediments of ODP Hole 178-1095B. 756 records from Herbario Nacional de Plantas Vasculares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 3 records from (Table T2) Dinoflagellate cyst occurrence in neogene sediments of ODP Hole 178-1096B. 20 records from (Table T2) Dinoflagellate cyst occurrence in neogene sediments of ODP Hole 178-1096C. 5 records from Microzooplankton abundance and biomass at station NBP97-03-03-5. 9 records from Microzooplankton abundance and biomass at station NBP97-03-04-5. 9 records from Microzooplankton abundance and biomass at station NBP97-03-05-6. 6 records from Microzooplankton abundance and biomass at station NBP97-03-06-8. 8 records from Microzooplankton abundance and biomass at station NBP97-03-07-8. 6 records from Microzooplankton abundance and biomass at station NBP97-03-08-2. 6 records from Microzooplankton abundance and biomass at station NBP97-03-09-1. 7 records from Microzooplankton abundance and biomass at station NBP97-03-10-10. 14 records from Microzooplankton abundance and biomass at station NBP97-03-11-1. 6 records from Microzooplankton abundance and biomass at station NBP97-03-12-2. 6 records from Microzooplankton abundance and biomass at station NBP97-03-13-2. 8 records from Microzooplankton abundance and biomass at station NBP97-03-14-3. 8 records from Microzooplankton abundance and biomass at station NBP97-03-16-1. 10 records from Microzooplankton abundance and biomass at station NBP97-08-02-10. 6 records from Microzooplankton abundance and biomass at station NBP97-08-03-3. 6 records from Microzooplankton abundance and biomass at station NBP97-08-04-5. 10 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 10 records from Microzooplankton abundance and biomass at station NBP97-08-06-4. 6 records from Microzooplankton abundance and biomass at station NBP97-08-07-1. 6 records from Microzooplankton abundance and biomass at station NBP97-08-08-1. 6 records from Microzooplankton abundance and biomass at station NBP97-08-09-1. 6 records from Microzooplankton abundance and biomass at station NBP97-08-13-1. 4 records from Microzooplankton abundance and biomass at station NBP97-08-16-3. 6 records from Microzooplankton abundance and biomass at station NBP97-08-19-1. 6 records from Microzooplankton abundance and biomass at station NBP97-08-23-6. 8 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 6 records from Microzooplankton abundance and biomass at station NBP97-08-28-1. 7 records from Microzooplankton abundance and biomass at station NBP97-08-29-1. 6 records from Microzooplankton abundance and biomass at station NBP97-08-31-7. 6 records from Microzooplankton abundance and biomass at station NBP97-08-32-1. 6 records from Microzooplankton abundance and biomass at station NBP97-08-33-5. 6 records from Microzooplankton abundance and biomass at station NBP97-08-34-1. 6 records from Microzooplankton abundance and biomass at station NBP97-08-35-5. 6 records from Microzooplankton abundance and biomass at station NBP97-08-36-1. 6 records from Microzooplankton abundance and biomass at station NBP97-08-37-4. 8 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-03-16. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-04-4. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-06-2. 5 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-10-12. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-11-5. 5 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-12-1. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-14-13. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-15-5. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-17-4. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-18-1. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-20-5. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-22-5. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-01-10. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-02-2. 2534 records from The First Comprehensive Description of the Biodiversity and Biogeography of Antarctic and Sub-Antarctic Intertidal Communities. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-03-7. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-04-1. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-10. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-9. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-06-4. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-07-5. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-08-9. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-09-1. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-10-2. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-4. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-14-2. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-15-3. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-17-7. 1 records from Cleveland Museum of Natural History.. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-18-5. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-19-2. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-20-3. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-23-2. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-25-2. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-28-3. 599 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Chavez 2011. 6 records from Erik Acharius lichen collection. 29 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/009-2. 21 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/011-3. 15 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/012-5. 18 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/014-4. 15 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/038-3. 1698 records from MNA Italica 2004_Rauschert dredge_Ross_sea_Mollusca_lgp. 14 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 23 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/042-2. 22 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/043-2. 19 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/045-2. 19 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/046-3. 18 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/048-3. 22 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/049-3. 19 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/061-3. 9 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/088-4. 16 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/090-4. 19 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/091-4. 21 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/092-3. 24 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/107-5. 21 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/108-1. 2 records from CAS Mammalogy (MAM). 75 records from Microzooplankton abundance measured on water bottle samples at station PS58/009-2. 62 records from Microzooplankton abundance measured on water bottle samples at station PS58/011-1. 68 records from Microzooplankton abundance measured on water bottle samples at station PS58/012-5. 66 records from Microzooplankton abundance measured on water bottle samples at station PS58/014-4. 62 records from Microzooplankton abundance measured on water bottle samples at station PS58/038-3. 56 records from Microzooplankton abundance measured on water bottle samples at station PS58/041-2. 67 records from Microzooplankton abundance measured on water bottle samples at station PS58/042-2. 69 records from Microzooplankton abundance measured on water bottle samples at station PS58/043-2. 70 records from Microzooplankton abundance measured on water bottle samples at station PS58/045-2. 88 records from Microzooplankton abundance measured on water bottle samples at station PS58/046-3. 65 records from Microzooplankton abundance measured on water bottle samples at station PS58/048-3. 69 records from Microzooplankton abundance measured on water bottle samples at station PS58/049-3. 70 records from Microzooplankton abundance measured on water bottle samples at station PS58/061-1. 68 records from Microzooplankton abundance measured on water bottle samples at station PS58/088-4. 63 records from Microzooplankton abundance measured on water bottle samples at station PS58/090-4. 57 records from Microzooplankton abundance measured on water bottle samples at station PS58/091-4. 72 records from Microzooplankton abundance measured on water bottle samples at station PS58/092-3. 71 records from Microzooplankton abundance measured on water bottle samples at station PS58/107-5. 63 records from Microzooplankton abundance measured on water bottle samples at station PS58/108-1. 25 records from UMMZ Mammal Collection. 229 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS1756-5. 401 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS1768-8. 34 records from Microzooplankton abundance measured on water bottle samples at station PS65/424-3. 33 records from Microzooplankton abundance measured on water bottle samples at station PS65/427-1. 55 records from Microzooplankton abundance measured on water bottle samples at station PS65/466-2. 56 records from Microzooplankton abundance measured on water bottle samples at station PS65/470-1. 37 records from Microzooplankton abundance measured on water bottle samples at station PS65/508-2. 25 records from Microzooplankton abundance measured on water bottle samples at station PS65/514-2. 51 records from Microzooplankton abundance measured on water bottle samples at station PS65/522-1. 51 records from Microzooplankton abundance measured on water bottle samples at station PS65/545-1. 22 records from Microzooplankton abundance measured on water bottle samples at station PS65/546-2. 30 records from Microzooplankton abundance measured on water bottle samples at station PS65/553-3. 26 records from Microzooplankton abundance measured on water bottle samples at station PS65/570-4. 31 records from Microzooplankton abundance measured on water bottle samples at station PS65/580-2. 22 records from Microzooplankton abundance measured on water bottle samples at station PS65/587-1. 32 records from Microzooplankton abundance measured on water bottle samples at station PS65/593-3. 6430 records from New Zealand Arthropod Collection (NZAC). 7 records from (Table 3+4) Abundance, biomass, production, and grazing of prokaryotes, nanoflagellates, ciliates, and dinoflagellates in three areas close to the Antarctic Peninsula in spring and summer 1995/96. 608 records from Relative abundances of late Quaternary benthic foraminifera in ODP Site 90-594. 20 records from (Table 1) Preservation and abundances of calcareous dinoflagellates in ODP Hole 113-689B. 132 records from (Fig. 2) Occurrence of calcareous dinoflagellate species in ODP Hole 113-689B. 464 records from (Fig. 3) Absolute abundance of dead benthic foraminifera in sediment core PS1394-3. 1214 records from (Table 6) Distribution of live benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 1. 54 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2247-1. 147 records from Benthic foraminifera and phytodetritus species in sediments from ODP Site 113-689. 46 records from Benthic foraminifera and phytodetritus species in sediments from ODP Site 113-690. 1429 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 1360 records from (Appendix table DR1) Foraminiferal distribution data for ODP Hole 178-1098B. 19 records from Table 1. Location, water depth, grain size distribution, organic carbon and carbonate contents of the investigated Arctic and Antarctic surface sediment samples. 233 records from (Appendix Table 3) Distribution of live benthic foraminifera in surface sediments. 405 records from (Appendix Table 4) Distribution of dead benthic foraminifera in surface sediments. 214 records from Benthos abundance in surface sediment sampled during cruise ANT-V/1. 1055 records from Macro benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 6697 records from Snow Petrel census, Reeve Hill, Windmill Island, East Antarctica (1984-2003). 57 records from Royal penguin Eudyptes schlegeli census, Macquarie Island, 1984. 1 records from Museu de Ciències Naturals de Barcelona: MCNB-ZG. 1815 records from RMT Trawl catch from the 1992/93 V6 KROCK voyage. 4 records from MfN - Fossil invertebrates III. 2 records from MfN - Fossil vertebrates IV. 6 records from MfN - Fossil plants (Mesophytic). 39 records from Relative abundance of radiolaria in surface sediments. 85 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 218 records from Distribution of main calcareous nannofossils at Site 1093. 11 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Ichthyology National Collection (MACNIct). 25 records from Coccolith percentage of surface sediment samples. 155 records from Coccolith percentage exclusive Emiliania huxleyi of surface sediment samples. 56 records from Ostracod species in Oligocene sediments of core CRP-2A. 14 records from Ostracod species in Oligocene sediments of core CRP-3. 45 records from Nannofossil abundance of Hole 28-265. 8 records from Nannofossil abundance of Hole 28-266. 16 records from SPF-Algae - Herbário da Universidade de São Paulo - Coleção de Algas. 115 records from Nannofossil abundance of Hole 29-279A. 5 records from Nannofossil abundance of Hole 29-280. 2 records from Nannofossil abundance of Hole 29-280A. 30 records from Nannofossil abundance of Hole 29-281. 353 records from UCT: South Africa Seaweeds(1905-2008). 4 records from Nannofossil abundance of Hole 29-281A. 125 records from (Appendix) Benthic foraminiferal abundance at DSDP Hole 71-511. 9 records from Nannofossil abundance of Hole 29-277. 67 records from Nannofossil abundance of Hole 29-278. 5 records from Nannofossil abundance of Hole 29-278A. 18 records from Nannofossil abundance of Hole 29-279. 32 records from SBMNH Vertebrate Zoology. 2 records from Bolus Herbarium Specimens Collection (1865-2009). 19 records from Nannofossil abundance of Hole 36-329. 15 records from Diatom abundance measured on water bottle samples at station PS58/009-2. 5 records from Diatom abundance measured on water bottle samples at station PS58/108-1. 7 records from Diatom abundance measured on water bottle samples at station PS58/107-5. 11 records from Diatom abundance measured on water bottle samples at station PS58/092-3. 15 records from Diatom abundance measured on water bottle samples at station PS58/090-4. 16 records from Diatom abundance measured on water bottle samples at station PS58/088-4. 11 records from Diatom abundance measured on water bottle samples at station PS58/061-3. 5 records from Diatom abundance measured on water bottle samples at station PS58/049-3. 9 records from Diatom abundance measured on water bottle samples at station PS58/048-3. 11 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 9 records from Diatom abundance measured on water bottle samples at station PS58/045-2. 13 records from Diatom abundance measured on water bottle samples at station PS58/042-2. 8 records from Diatom abundance measured on water bottle samples at station PS58/041-2. 9 records from Diatom abundance measured on water bottle samples at station PS58/038-3. 10 records from Diatom abundance measured on water bottle samples at station PS58/014-4. 12 records from Diatom abundance measured on water bottle samples at station PS58/012-5. 12 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 8 records from Diatom abundance measured on water bottle samples at station PS58/091-4. 5 records from Diatom abundance measured on water bottle samples at station PS58/043-2. 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/009-2. 7 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/011-3. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/012-5. 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/038-3. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/041-2. 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/043-2. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/045-2. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/046-3. 3 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/049-3. 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/061-3. 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/088-4. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/090-4. 7 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/091-4. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/092-3. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/107-5. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/108-1. 11 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/009-2. 17 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/011-3. 16 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/012-5. 11 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/014-4. 9 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/038-3. 8 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/041-2. 14 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/042-2. 9 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/043-2. 13 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/045-2. 13 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/046-3. 14 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/048-3. 14 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/049-3. 9 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/061-3. 10 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/088-4. 7 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/090-4. 9 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/091-4. 12 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/092-3. 4 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/107-5. 10 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/108-1. 18 records from (Table 1) Early Miocene and late Oligocene ostracods in sediment core CRP-2A. 79 records from (Table 2) Quarternary ostracod abundance in sediment core CRP-1. 23 records from Colección de Entomología - Curculionidae. 2 records from Enigmas from the past: M’Intosh’s (1885) annelidicolous copepods from the voyage of H. M. S. Challenger. 1 records from ASE - Herbário da Universidade Federal de Sergipe. 32 records from CM Herps Collection. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/424-3. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/427-1. 7 records from Phytoplankton abundance measured on water bottle samples at station PS65/466-2. 86 records from UEC - Herbário da Universidade Estadual de Campinas. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/470-1. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/508-2. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/514-2. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/522-1. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/545-1. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/546-2. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/553-3. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/570-4. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/580-2. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/587-1. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/593-3. 100 records from (Table 2) Ostracode assemblages and environment characteristica of modern surface sediment samples from Patagonia, Argentina. 419 records from (Table 2) Abundance of ostracods in surface sediment samples from the Admiralty Bay, King George Island, West Antarctica. 1892 records from Physical properties and geochemical composition of sediment cores PTA02-04, PTA03-12 and PTA03-13 from Laguna Potrok Aike, Patagonia. 964 records from (Appendix B) Nannofossil abundances in DSDP Hole 90-594 from the South Chatham Rise, southeastern New Zealand. 785 records from (Appendix I) Distribution of Quaternary nannoflora at DSDP Site 90-594 east of South Island, Southwest Pacific. 24 records from (Table 2) Documentation of vital effect change in Coccolitophorides above the FAD Emiliania huxleyi in DSDP Site 90-594 east of South Island, Southwest Pacific. 19 records from (Table 2) Range chart of calcareous nannofossils from Maud Rise sediment cores. 54 records from (Table 3) Range chart of calcareous nannofossils from Weddell and Bellingshausen Sea sediment cores. 28 records from (Table 4) Range chart of calcareous nannofossils from Ross Sea sediment cores. 818 records from Range chart of calcareous nannofossils from ODP Hole 188-1165B (Table 1). 66 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 113-689. 82 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 114-699. 48 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 114-703. 56 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 119-744. 116 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 120-748. 28 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of ODP Hole 189-1171D. 2634 records from Mega benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 133251 records from NZ National Vegetation Survey occurrence data. 42 records from FUEL - Herbário da Universidade Estadual de Londrina. 16 records from MSB Parasite Collection (Arctos). 2 records from Hydrolagus erithacus sp. nov. (Chimaeriformes: Chimaeridae), a new species of chimaerid from the southeastern Atlantic and southwestern Indian oceans. 1025 records from (Table DR1) Abundance of benthonic foraminifera in sediments from ODP Hole 113-690. 206 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 17 records from (Table 1) Mineralogy of ODP Hole 113-692B. 117 records from Northern Territory Museum and Art Gallery provider for OZCAM. 19 records from Plankton abundance measured in surface water during Polarstern cruise ANT-XX/2. 4 records from Estimated plankton abundance at station PS63/064-6. 177 records from Lichen herbarium, Oslo (O). 1295 records from Planktic foraminifera counts of sediment core RC08-49. 1 records from ICN - Universidad Nacional de Colombia. 201 records from (Table 2) Relative abundances of calcareous nannofossils in ODP Hole 120-748A. 355 records from Sightings of marine mammals carried out during oceanographic surveys in the Argentine continental shelf. 5841 records from (Table 1) Ranges of Paleocene to middle Eocene planktonic foraminifera in ODP Hole 119-738B. 4189 records from (Table 2) Ranges of middle Eocene through Holocene planktonic foraminifera in ODP Hole 119-738C. 9660 records from (Table 3) Ranges of upper Eocene Holocene planktonic foraminifera in ODP Hole 119-744A. 480 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 64 records from (Table 2) Distribution of calcareous nannofossils in ODP Hole 119-738C. 250 records from (Appendix) Relative abundance of some calcareous nannofossils in ODP Hole 119-738C. 900 records from Occurrence of dinoflagellate cysts in ODP Hole 119-738C (Appendix). 6348 records from (Table 1) Distribution of benthic foraminifera in ODP Site 120-747. 777 records from (Table 2) Distribution of benthic foraminifera in ODP Hole 120-748A. 8216 records from (Table 4) Distribution of benthic foraminifera in ODP Site 120-750. 103 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 1610 records from (Appendix A) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-747A. 1530 records from (Appendix B) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-747C. 3224 records from (Appendix C) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-748B. 945 records from (Appendix D) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-748C. 1850 records from (Appendix E) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-749B. 126 records from (Appendix F) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-749C. 983 records from (Table 2) Distribution of planktonic foraminifera in the larger size fraction of ODP Hole 120-747A. 1336 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 243 records from (Table 3) Distribution of planktonic foraminifera in the larger size fraction of ODP Hole 120-749B. 287 records from (Table 3) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-749B. 536 records from (Table 1) Absolute abundances of benthic foraminifera in ODP Site 120-747. 1039 records from (Table 3) Relative abundances of benthic foraminifera in ODP Site 120-748. 473 records from (Table 3) Relative abundances of benthic foraminifera in ODP Site 120-747. 1158 records from (Table 2) Absolute abundances of benthic foraminifera in ODP Site 120-748. 2553 records from (Appendix A) Stratigraphic range and relative abundance of Neogene planktonic foraminifer taxa in ODP Hole 120-747A. 2349 records from (Appendix B) Stratigraphic range and relative abundance of Neogene planktonic foraminifer taxa in ODP Hole 120-748B. 2750 records from (Appendix C) Stratigraphic range and relative abundance of Neogene planktonic foraminifer taxa in ODP Hole 120-751A. 1 records from AlgaTerra. 890 records from RMT Trawl catch from the 2005/06 V3 BROKE-West voyage - Zooplankton. 8916 records from LACM Vertebrate Collection. 1 records from Natural History Museum Rotterdam (NL) - Chordata collection. 7 records from Colección Nacional de Equinodermos Mexicanos (ICMyL-DF, UNAM). 8 records from Museu de Ciències Naturals de Barcelona: MCNB-Art. 48 records from Estación Experimental de Zonas Áridas (CSIC): EEZA-Herpet. 12 records from Collection Crustacea ZMG. 2 records from Insecta ZMK. 1 records from Jardin botanique de Montréal (JBM). 243 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 23114 records from SOMBASE BIOCONSTRUCTORS. 83 records from Admiralty Bay Benthos Diversity Data Base (ABBED). Cumacea.. 24 records from Admiralty Bay Benthos Diversity Data Base (ABBED). Polychaeta. 1979-80. 28 records from Admiralty Bay Benthos Diversity Data Base (ABBED). Pycnogonida.. 90 records from Admiralty Bay Benthos Diversity Data Base (ABBED). Tanaidacea.. 21 records from IZIKO South Africa Museum Collection (1800-2013). 942 records from Amphipoda Hyperiidea of the Southern Ocean: catalogue and occurrences. 1406 records from Biogeographic distribution of the Antarctic and Sub-Antarctic brachiopods (living forms). 1417 records from Biogeographic distribution of Antarctic and sub-Antarctic Cumacea. 3956 records from Antarctic Jellyfish. 36 records from Antarctic and sub-Antarctic Lophogastrida occurrences. 1 records from Antarctic Marine Amoebae. 51 records from Antarctic Marine Bacteria from Denmark University. 705 records from Biogeographic distribution of Antarctic and sub-Antarctic Mysida. 439 records from Antarctic and Subantarctic Asteroid zoogeography. 770 records from Marine birds and mammals of the Southern Ocean (a census for the CAML). 4717 records from Weddell Sea macrozoobenthos EASIZ I. 3855 records from Icota - Pelagant. 310 records from Museo Argentino de Ciencias Naturales (MACN), Buenos Aires: sea stars collection (Asteroidea, Echinodermata). 623 records from MNA - Sezione di Genova - (Marine Biological Samples). 43 records from Antarctic Isopods. 110 records from Antarctic Pycnogonids II. 1 records from Bacteria from Penguin Guano, Antarctica. 276 records from Mitochondrial lineages in the Antarctic sea slug Doris kerguelenensis. 422 records from Antarctic Krill Euphausia superba. 173 records from Antarctic Foraminiferans. 162 records from Antarctic fish Gobionotothen gibberifrons. 174 records from Antarctic pycnogonids. 240 records from Antarctic Marine Species Sequence Data. 104 records from Ross Sea Pycnogonids. 102 records from Antarctic Parborlasia corrugatus. 5 records from Penguins of Antarctica. 114 records from Promachocrinus kerguelensis. 909 records from South American Antarctic Marine Biodiversity Literature. 879 records from Asteroids from French subantarctic islands: records from the Marion Dufresne MD03 expeditions. 4732 records from SO-Polylist. 30 records from Southern Ocean oligochaete occurrence data - a literature-based compilation. 78 records from In situ observations of Stygiomedusa gigantea. 117 records from SOVIET ANTARCTIC EXPEDITIONS for Zooplankton (R.V. OB March-May 1956, January-March 1957;R.V.ACADEMIC KURCHATOV, October 1971-January 1972; RV DMITRY MENDELEEV;R.V.ACADEMIC IOFFE 1992).. 936 records from RMT Trawl catch from the 1982/83 V2 ADBEX I voyage. 138 records from RMT Trawl catch from the 1983/84 V5 ADBEX II voyage. 2427 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 746 records from RMT Trawl catch from the 1986/87 V7 AAMBER voyage. 1212 records from RMT Trawl catch from the 1990/91 V6 AAMBER2 voyage. 10 records from Collection Bryozoa - ZIM Hamburg. 1 records from Collection Cnidaria - ZIM Hamburg. 620 records from Collection Crustacea - ZIM Hamburg. 21 records from Collection Oligochaeta - ZIM Hamburg. 439 records from Collection Polychaeta - ZIM Hamburg. 13 records from Collection Hydrozoa - ZSM München. 52 records from Collection Bryozoa - ZMB. 27 records from Collection Cnidaria - ZMB. 468 records from Collection Crustacea - ZMB. 71 records from Collection Echinodermata - ZMB. 32 records from Collection Hydrozoa - ZMB. 85 records from Collection Porifera - ZMB. 54 records from Collection Vermes - ZMB. 1 records from Collection Ornithologie - ZSRO. 16 records from Collection Polychaeta - ZSRO. 2 records from Tiroler Landesmuseum Ferdinandeum. 17 records from The Fungal Collection at the Botanische Staatssammlung München. 1800 records from Ant'Phipoda Database (New records). 103454 records from ANTAVIA-TrackingKing. 118 records from Antarctic Amphipoda. 106 records from Antarctic Nemertea. 3 records from Antarctic Arrow worms. 3 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 68 records from The Lichen Collection at the Botanische Staatssammlung München. 554 records from The Fungal and Lichen Collections at the Herbarium Marburgense. 1 records from Estación Experimental de Zonas Áridas (CSIC) EEZA - Aves. 1 records from Natural History Museum Rotterdam (NL) - Invertebrata miscellaneous Collection. 4740 records from Tropicos Specimen Data. 50926 records from British Antarctic Survey Argos satellite tracking data. 6384 records from SOMBASE PYCNOGONIDS. 21 records from (Table S1) Relative abundances of coccolithophore taxa in surface sediment samples from the Equatorial and Southeastern Pacific. 9 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-7. 13 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-9. 2 records from New species and records of Zavreliella Kieffer, 1920 from Neotropical region (Diptera: Chironomidae). 18 records from (Table 1.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Polarstern cruise ANT-XXIII/7. 26 records from (Table 2.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Aurora Australis cruise SIPEX. 159 records from Natural History Museum Rotterdam (NL) - Mollusca collection. 396 records from Western Australian Museum provider for OZCAM. 12 records from (Table 9) Relative abundance of calcareous nannofossil species across the Cretaceous/Paleocene boundary at ODP Hole 120-750A. 3 records from (Table T1) Lithology and palynomorphs of neogene sediments of ODP Hole 178-1096C. 2 records from (Table T1) Lithology and palynomorphs of neogene sediments of ODP Hole 178-1096B. 15 records from (Table T1) Lithology and palynomorphs of neogene sediments of ODP Hole 178-1095B. 282 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 110 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD3. 415 records from (Table 1) Distribution of Lower Cretaceous calcareous nannofossils in ODP Hole 113-692B. 206 records from (Table 2) Distribution of Lower Cretaceous calcareous nannofossils in ODP Hole 113-693A. 113 records from Survey of benthic and other marine invertebrates of Prydz Bay, 1990/91 Voyage 6. 360 records from (Figure 6) Range chart of planktonic foraminifers across the K/T boundary at ODP Hole 120-750A. 121 records from Table II: Birds observed at the Weddell Sea during the period: 22 December 1959 to 14 January 1960. 372 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 348 records from (Table 2) Distribution of planktonic foraminifera in ODP Hole 183-1136A. 350 records from (Table 4) Abundance of planktonic foraminifera in ODP Hole 113-690C, small size fraction. 240 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part I. 20 records from Biology and population studies of two endemic orchid species on sub-Antarctic Macquarie Island. 1 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/567-1. 615 records from (Table 1) Distribution of planktonic foraminifera in ODP Hole 183-1135A, Part I. 49 records from Abundance of calcareous nannofossils across the K/T boundary at ODP Hole 113-690C (Table 1). 1 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/574-1. 410 records from (Table 1) Distribution of planktonic foraminifera in ODP Hole 183-1135A, Part II. 3005 records from Annotated Atlas of the Vascular Flora of Macquarie Island - 1979. 17 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-13. 471 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part III. 173 records from Late Cretaceous ostracods recorded from ODP Hole 113-689B. 8 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-3. 10 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-14. 13 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-11. 2 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 15 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-2. 3 records from Integrative taxonomic re-description of Halisarca magellanica and description of a new species of Halisarca (Porifera, Demospongiae) from Chilean Patagonia. 3378 records from (Appendix 1) Census data of planktic foraminiferal faunas together with estimates of mean annual SST for DSDP Site 90-594. 52 records from Squid collection from 1995/96 V4 BROKE. 136 records from SysTax - Zoological Collections. 1115 records from (Table 6) Distribution of live benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 2. 1211 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 2. 1561 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 1. 1 records from Chaetognatha - SMF. 1 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/554-2. 195 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction. 221 records from (Table 1) Abundance of planktonic foraminifera in ODP Hole 113-689B, large size fraction. 432 records from (Table 3) Occurrence of dinocyst species in ODP Hole 113-692B. 4 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/549-2. 23 records from (Table 4) Relative abundance of the major nannofossil groups in the Lower Cretaceous of ODP Hole 113-693A. 1 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/565-1. 181 records from Table I: Birds observed at the Weddell Sea during the period: 6 December 1955 to 19 January 1956. 10 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-10. 12 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-1. 2 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-6. 300 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part II. 2167 records from SOUTHERN OCEAN ISOPODA. 301 records from Southern Ocean Cnidarian Collections. 8327 records from Southern Ocean octopus. 5733 records from Natural History Museum (London) Collection Specimens. 11737 records from (Appendix II) Planktonic foraminiferal biostratigraphy of ODP Site 113-690. 20 records from Distribution of planktonic foraminifera and other biogenic components in ODP Hole 113-693A (Figure 2). 11220 records from (Appendix I) Planktonic foraminiferal biostratigraphy of ODP Hole 113-689B. 18894 records from (Table 5) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Site 114-702. 14278 records from (Table 4) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-700B. 15494 records from (Table 6) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-703A. 1 records from A taxonomic revision of the ground spiders of the genus Apopyllus (Araneae: Gnaphosidae). 2464 records from (Table 2) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-698A. 11340 records from (Table 3) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-699A. 256 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B. 6391 records from (Table 3) Planktonic foraminifers from ODP Hole 114-704A. 1148 records from (Table 4) Planktonic foraminifers from ODP Hole 114-704B. 468 records from (Table 3) Occurrence of dinoflagellate cyst species in ODP Hole 113-696B. 4175 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 2785 records from (Appendix 2, Part 3) Distribution of Eocene to Recent benthic foraminifera in ODP Site 113-690. 1241 records from (Appendix 2, Part 2) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-689. 124 records from (Table 5) Distribution of calcareous nannofossils in the Paleocene of ODP Hole 113-690C. 66 records from (Table 2) Distribution of calcareous nannofossils in the Paleocene of ODP Hole 113-689B. 32 records from (Table 1) Distribution of calcareous nannofossils in the Eocene of ODP Hole 113-689B. 96 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 113-689B. 117 records from (Table 2) Distribution of calcareous nannofossils in ODP Hole 113-690C. 1473 records from (Appendix 2, Part 1) Distribution of Eocene to Recent benthic foraminifera in ODP Site 113-689. 114 records from (Table 1) Calcareous nannofossil distribution and relative abundance in ODP Hole 114-699A. 26 records from (Table 4) Mean values of the chemical data from the ash layers from ODP Legs 113 and 114. 29 records from (Table 2) Distribution of Eocene to Paleocene calcareous nannofossils in ODP Hole 114-699A. 126 records from (Table 2) Calcareous nannofossil distribution and relative abundance in ODP Hole 114-703A. 152 records from (Table 1) Numerical abundance counts of planktonic foraminifers and other biogenic constituents for ODP Hole 114-698A. 280 records from (Table 2) Numerical abundance counts of planktonic foraminifers and other biogenic constituents for ODP Hole 114-700B. 318 records from (Table 3) Distribution and relative abundance of planktonic foraminifers in ODP Hole 114-704A. 19 records from (Table 4) Distribution and relative abundance of planktonic foraminifers in ODP Hole 114-704B. 18 records from (Table 2) Distribution and relative abundance of planktonic foraminifers in ODP Hole 114-703A. 140 records from Distribution of late Turronian planktonic foraminifers in ODP Hole 114-700B. 206 records from Natural History Museum, Vienna - Herbarium W. 228 records from Cetacean Sightings Survey and Southern Ocean Cetacean Program - BROKE-West. 324 records from Phytoplankton samples - 2001/02 V3 CLIVAR. 190 records from Phytoplankton samples - 2001/02 V7 LOSS. 234 records from Phytoplankton samples - 2006/07 V3 SAZ-Sense. 708 records from Phytoplankton samples - 2005/06 V3 BROKE-West. 1505 records from Macaulay Library Audio and Video Collection. 3 records from Plathelminthes - SMF. 1 records from Computarización del Herbario ENCB, IPN. Fase IV. Base de datos de la familia Pinaceae y de distintas familias de la clase Magnoliopsida depositadas en el Herbario de la Escuela Nacional de Ciencias Biológicas, IPN. 2 records from UAM Insect Collection (Arctos). 33 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 2 records from UAM Invertebrate Collection (Arctos). 3 records from RBINS collections. 159 records from (Table 1) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Site 120-747. 1634 records from (Table 2) Stratigraphic occurrences of the dinoflagellate cysts in lithologic Subunit IIIB of ODP Hole 120-748C. 116 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C. 38 records from (Table 1) Chiasmolithus species and intermediate forms of ODP Holes 105-647A and 120-748B. 6290 records from (Table 1) Dinoflagellate range chart of ODP Hole 120-748C. 1674 records from (Table 3) Neogene benthic foraminifers of ODP Hole 120-751A. 28 records from Phythoplankton abundance and biomass measured on water bottle samples during POLARSTERN cruise ANT-X/6. 1239 records from (Table 1) Neogene benthic foraminifers of ODP Hole 120-747A. 22 records from Phythoplankton abundance measured on water bottle samples during POLARSTERN cruise ANT-X/6. 515 records from (Table 2) Neogene benthic foraminifers of ODP Hole 120-748B. 67 records from Nekton and plankton counts from Wechselnetz-Hai (300 µm) hauls of cruise GAE 1975/76. 3538 records from (Table 4) Paleocene to Eocene planktonic foraminifera of DSDP Hole 29-277. 1092 records from (Table 5) Oligocene planktonic foraminifera of DSDP Hole 29-277. 187 records from Field Museum of Natural History (Botany) Fungi Collection. 1215 records from (Figure 2) Distribution of planktonic foraminifers in the Albian of DSDP Hole 71-511. 6930 records from (Figure 3) Distribution of planktonic foraminifers in the Upper Cretaceous of DSDP Hole 71-511. 2784 records from (Figure 3) Distribution of benthic foraminifers in the Albian of DSDP Hole 71-511. 6006 records from (Table 5) Distribution of benthic foraminifers in the late Cretaceous of DSDP Hole 71-511. 2904 records from (Figure 8) Distribution of benthic foraminifers in the Pliocene-Quaternary of DSDP Hole 71-514. 11700 records from (Figure 4) Distribution of benthic foraminifers in the Upper Cretaceous of DSDP Hole 71-511. 1620 records from (Figure 5) Distribution of planktonic foraminifers in the Cenozoic sediments of DSDP Hole 71-513. 245 records from (Table 2) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Hole 120-748C. 426 records from (Table 3) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Site 120-750. 601 records from Nekton and plankton counts from RMT (320 µm) hauls of cruise GAE 1975/76. 252 records from Nekton and plankton counts from neuston net (300 µm) hauls of cruise GAE 1975/76. 45 records from Nekton and plankton counts from bongo net (300, 500 µm) hauls of cruise GAE 1975/76. 861 records from (Table 1) Percentage of Coccolithus pelagicus vs. Reticulofenestra spp. of ODP Hole 120-747A. 47 records from Distribution of calcareous nannofossils in the lower sequence of the CIROS-1 sediment core (Table 2). 71839 records from NMNH Extant Specimen and Observation Records. 157 records from ARC-PPRI: National Survey of Arachnida (1905-2009). 156 records from (4) Assemblages of planktic foraminifera and Sea Surface Temperature (SST) reconstructed from the Modern Analogue Technique in sediment core MD02-2488 during the Last Interglacial. 186 records from (3) Sea Surface Temperature (SST) reconstructed from the percentage of Neogloboquadrina pachyderma sinistral in sediment core MD02-2488 during the period 50-140 ka. 2 records from DSMZ Collection of Filamentous Fungi and Yeasts. 750 records from (Table 20) Benthic foraminifera in early Miocene sediments of DSDP Hole 90-594. 376 records from Herbarium Senckenbergianum (FR) - Fungi. 8 records from Collection Malakologie - SNSD. 3 records from Collection Anatomie Histologie - SMF. 15 records from Edaphobase. 9 records from Partial Amphibians Collection. 663 records from Swiss Psyllid (Hemiptera) Collections - Geneva. 23 records from Swiss Psyllid (Hemiptera) Collections - Basel. 6 records from Parasitic Platyhelminthes Collections. 14431 records from SOMBASE. 50706 records from ANTARCTIC PLANT DATABASE. 38 records from Fungal Biodiversity Centre (CBS) - Fungi strains. 142397 records from Seabirds of the Southern and South Indian Ocean. 9190 records from Weddell Seal census, Vestfold Hills, Antarctica. 20992 records from Weddell Seal Sightings, Vestfold Hills, Antarctica. 1794 records from Elephant Seal Sightings, Heard Island. 120000 records from Elephant Seal Sightings, Macquarie Island. 7122 records from Whale catches in the Southern Ocean. 11153 records from Australian Antarctic Division Herbarium. 340530 records from ARGOS Satellite Tracking of animals. 90 records from National Whale and Dolphin Sightings and Strandings Database. 248 records from Orca observations from the shores of Macquarie Island. 125880 records from Southern Ocean Continuous Zooplankton Recorder (SO-CPR) Survey. 1068 records from Cetacean Sightings Survey and Southern Ocean cetacean program. 9271 records from APIS - Antarctic Pack Ice Seals 1994-1999, plus historical data from the 1980's. 924 records from Antarctic Fur Seal Populations on Heard Island Summer 1987-1988. 11542 records from Macquarie Island Fur Seal Database. 4 records from Canadian Museum of Nature Herbarium. 28 records from UWBM Mammalogy Collection. 501 records from UWBM Ornithology Collection. 33 records from UWFC Ichthyology Collection. 4 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 58 records from The AAU Herbarium Database. 1 records from Revision of the South American genus Tetragonopterus Cuvier, 1816 (Teleostei: Characidae) with description of four new species. 151 records from Real Jardin Botanico, Madrid: MA-Musci. 2 records from Real Jardin Botanico, Madrid: MA-Lichen. 474 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 254 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 83 records from Herbario de la Universidad de Sevilla. 2 records from CUBA:Herbario del Jardín de los Helechos, Centro Oriental de Ecosistemas y Biodiversidad, Santiago de Cuba: BSC-Pteridophyta. 3 records from HMAP-History pf Marine Animal Populations (CoML). 45781 records from NODC WOD01 Plankton Database. 13 records from SeamountsOnline (seamount biota) (CoML). 7 records from Natural Geography In Shore Areas (NaGISA) Dataset. 1 records from Bishop Museum Data (OBIS distribution) (USOBIS). 542 records from Generic Taxonomic Database System on Mysida and Nematoda. 52 records from Academy of Natural Sciences OBIS Mollusc Database. 28366 records from SEAMAP - marine mammals, birds and turtles. 1297 records from Hexacoral Database. 13927 records from Auckland Museum Botany Collection. 58911 records from ``South Western Pacific Regional OBIS Data provider for the NIWA Marine Biodata Information System``. 2 records from ChEssBase (CoML). 1 records from Taxonomic Information Sytem for the Belgian coastal area (EurOBIS). 765 records from Locations of seals in Patagonian Large Marine Ecosystem (OBIS South America, AR-OBIS, Sub-node). 1248 records from Demersal and pelagic species of fish and squid from the Patagonian shelf. 2623 records from Fishes in the Argentine Sea from 1967 to the present time. 24 records from AIMS - Bioresources Library (OBIS Australia). 391 records from iziko South African Museum - Fish Collection (AfrOBIS). 83 records from iziko South African Museum - Marine Mammal Collection (AfrOBIS). 428 records from FPN-EH-AVES - Breeding Distribution of seabirds in Patagonia Argentina coast. 76 records from iziko South African Museum - Shark Collection (AfrOBIS). 2 records from Bolus Herbarium Algal Specimen Database (AfrOBIS). 324 records from iziko South African Museum - Mollusc Collection (AfrOBIS). 64 records from Distribution ashore and breeding places of southern elephant seals. 974 records from Cetacean distribution in the South Atlantic and South Pacific Ocean (AR-OBIS). 29704 records from MICROBIS database. 746 records from Polycystine Radiolarians from the water column and the surface sediments of the World Ocean. 1166 records from Distribution of nematodes in Patagonia Argentina coast (OBIS South America, SOUTHERN OCEAN SUB-NODE). 14 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 7501 records from Michigan State University Herbarium Lichens. 14 records from BYU Herpetology Collection. 10986 records from Paleobiology Database. 324 records from (Appendix B) Planktic foraminiferal assemblages from ODP Holes 113-689B and 113-690B. 8 records from Fish collection of National Museum of Nature and Science. 15 records from NBM birds. 8 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 3 records from Mammals Specimens. 79 records from SDNHM Birds Collection. 1 records from SDNHM Herpetology Collection. 580 records from Arizona State University Lichen Collection. 52 records from Galathea II, Danish Deep Sea Expedition 1950-52. 1 records from Western Palearctic migratory birds in continental Africa. 3 records from Botanical Museum, Copenhagen, the Lichen Herbarium. 1 records from Botanical Museum, Copenhagen. Database of type specimens. 41 records from DAV UC Davis Center for Plant Diversity. 5 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 2 records from CNMA/Colección Nacional de mamíferos. 2 records from MEXU/Plantas Vasculares. 337 records from MEXU/Colección de Briofitas. 17 records from CNCR/Colección Nacional de Crustaceos. 10 records from Plants of Papua New Guinea. 267 records from Mammal specimens. 54 records from MMNH Museum Bird Collection. 283 records from Invertebrate Paleontology Division, Yale Peabody Museum. 1035 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 1812 records from Invertebrate Zoology Division, Yale Peabody Museum. 4 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 23 records from TTU Mammals Collection. 54 records from (Table 10) Eocene-Oligocene diatom biostratigraphy of ODP Hole 120-748B. 59 records from Algaterra Types. 1 records from Herbarium Berolinense. 212 records from Lichen Herbarium Berlin. 1 records from Centre for Genetic Resources, the Netherlands, PGR passport data. 107 records from Biologiezentrum Linz. 469 records from United States National Plant Germplasm System Collection. 3 records from The System-wide Information Network for Genetic Resources (SINGER). 63 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 4 records from The Erysiphales Collection at the University Halle-Wittenberg. 3 records from The Myxomycetes Collections at the Botanische Staatssammlung München - Main Collection. 9 records from IndOBIS, Indian Ocean Node of OBIS. 117 records from Nordic Genetic Resources. 15 records from USU-UTC Specimen Database. 3807 records from Planetary Biodiversity Inventory Eumycetozoan Databank. 53396 records from Pelagic Fish Observations 1968-1999. 12 records from UF Invertebrate Zoology. 80 records from The Collection of Fungi of the Real Jardín Botánico of Madrid (MA-Fungi). 1 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-HEPATICAE. 80 records from Fish Collection of Natural History Museum and Institute, Chiba. 47 records from The Myxomycetes Collection at the V. L. Komarov Botanical Institute, St. Petersburg. 723 records from South Western Pacific Regional OBIS Data Asteroid Subset (South Western Paci fic OBIS). 1166 records from South Western Pacific Regional OBIS Data Bio Ross Subset (South Western Pac ific OBIS). 1151 records from South Western Pacific Regional OBIS Data Bryozoan Subset (South Western Paci fic OBIS). 9941 records from South Western Pacific Regional OBIS Data All Sea Bio Subset (South Western P acific OBIS). 2825 records from Inventory of Antarctic seabird breeding sites. 1282 records from Electron Micrograph Database - Marine Specimens. 341 records from Electron Micrograph Database - Terrestrial and Limnetic Specimens. 118 records from Kelp rafts in the Southern Ocean. 1 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 99 records from Harvard University Herbaria. 1 records from UCLA Donald R. Dickey Bird and Mammal Collection. 25 records from DSMZ Prokarya Collection Catalogue. 2314 records from RMT Trawl catch from the 1980/81 V5 FIBEX voyage. 556 records from RMT Trawl catch from 1985/86 V1 ADBEX III voyage. 2760 records from RMT Trawl catch from the 1995/96 V4 BROKE voyage. 359 records from Marine fauna survey of the Vestfold Hills and Rauer Island, 1981-82. 120 records from EURISCO, The European Genetic Resources Search Catalogue. 1282 records from Electron Micrograph Database (Australian Antarctic Data Centre). 25912 records from Pelagic Fish Observations 1968-1999 (Australian Antarctic Data Centre). 118 records from Kelp rafts in the Southern Ocean (Australian Antarctic Data Centre). 359 records from Marine fauna survey of the Vestfold Hills and Rauer Island, 1981-82 (Australian Antarctic Data Centre). 1020 records from RMT Trawl catch from 1985/86 V1 ADBEX III voyage (Australian Antarctic Data Centre). 4380 records from RMT Trawl catch from the 1980/81 V5 FIBEX voyage (Australian Antarctic Data Centre). 29 records from Coleção Entomológica Pe. Jesus Santiago Moure (Hymenoptera). 519 records from MAL. 603 records from Diatoms from the Vestfold Hills Lakes. 1883 records from AAD Benthic Sampling Database. 1792 records from Planktic foraminifera assemblage of sediment core ELT49.017-PC. 2320 records from Planktic foraminifera assemblage of sediment core ELT49.018-PC. 755 records from Planktic foraminifera assemblage of sediment core ELT49.023-PC. 1873 records from Planktic foraminifera counts in surface sediment samples. 64 records from Distribution of planktonic foraminifera in surface sediment samples A180-072 to V23-83. 389 records from (Table 2) Distribution of planktonic foraminifera in DSDP Hole core 90-594. 194 records from (Table 2) Sea surface temperature reconstruction from sediment core MD88-770. 997 records from Modern planktic foraminifera assemblage from surface sediment samples used as reference data set for the reconstruction of Atlantic sea surface temperatures during the last glacial maximum (LGM). 346 records from Distribution of planktic foraminifera in surface sediment samples from cruise SO136. 1554 records from Composition of planktonic foraminifera species in 1123 surface sediment samples compared with sea surface temperatures from the Levitus Atlas. 87 records from Composition of planktonic foraminifera species from 310 sediments samples during the last glacial maximum. 336 records from Distribution of planktic foraminifera in surface sediments of the Atlantic Ocean (ATL947). 671 records from Foraminifera and stable isotopes of sediment core PS1754-1. 343 records from Planktic foraminifera assemblage in sediment core Q208. 628 records from Abundance of planktonic foraminifera in surface sediments of the South Atlantic. 392 records from Relative abundances of planktonic foraminifera from surface sediments of the Drake Passage, Southern Ocean (Table 1). 57 records from Relative abundance of recycled Pliocene foraminifera of sediment core CRP-1 (App. 1). 497 records from Relative abundance of Quaternary foraminifera of sediment core CRP-1 (App. 1). 3 records from Analyses of the recent components of sediment core PS1010-1. 5 records from Analyses of the recent components of sediment core PS1012-1. 9 records from Analyses of the recent components of sediment core PS1013-1. 5 records from Analyses of the recent components of sediment core PS1014-1. 2 records from Analyses of the recent components of sediment core PS1016-1. 3 records from Analyses of the recent components of sediment core PS1215-2. 5 records from Analyses of the recent components of sediment core PS1216-1. 9 records from Analyses of the recent components of sediment core PS1217-1. 7 records from Analyses of the recent components of sediment core PS1219-1. 7 records from Analyses of the recent components of sediment core PS1220-3. 7 records from Analyses of the recent components of sediment core PS1222-1. 5 records from Analyses of the recent components of sediment core PS1400-4. 3 records from Analyses of the recent components of sediment core PS1401-2. 7 records from Analyses of the recent components of sediment core PS1402-2. 3 records from Analyses of the recent components of sediment core PS1403-1. 5 records from Analyses of the recent components of sediment core PS1422-1. 3 records from Analyses of the recent components in the sand fraction of sediment core PS1010-1. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1012-1. 9 records from Analyses of the recent components in the sand fraction of sediment core PS1013-1. 3 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1016-1. 3 records from Analyses of the recent components in the sand fraction of sediment core PS1215-2. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1216-1. 9 records from Analyses of the recent components in the sand fraction of sediment core PS1217-1. 7 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 7 records from Analyses of the recent components in the sand fraction of sediment core PS1220-3. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1222-1. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1400-4. 3 records from Analyses of the recent components in the sand fraction of sediment core PS1401-2. 7 records from Analyses of the recent components in the sand fraction of sediment core PS1402-2. 3 records from Analyses of the recent components in the sand fraction of sediment core PS1403-1. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1422-1. 3 records from Analyses of the recent components of sediment core PS1010-1. 5 records from Analyses of the recent components of sediment core PS1012-1. 9 records from Analyses of the recent components of sediment core PS1013-1. 5 records from Analyses of the recent components of sediment core PS1014-1. 5 records from Analyses of the recent components of sediment core PS1016-1. 3 records from Analyses of the recent components of sediment core PS1215-2. 1781 records from Naturalis Biodiversity Center (NL) - Aves. 5 records from Analyses of the recent components of sediment core PS1216-1. 9 records from Analyses of the recent components of sediment core PS1217-1. 7 records from Analyses of the recent components of sediment core PS1219-1. 3 records from Analyses of the recent components of sediment core PS1220-3. 7 records from Analyses of the recent components of sediment core PS1222-1. 5 records from Analyses of the recent components of sediment core PS1400-4. 3 records from Analyses of the recent components of sediment core PS1401-2. 7 records from Analyses of the recent components of sediment core PS1402-2. 3 records from Analyses of the recent components of sediment core PS1403-1. 5 records from Analyses of the recent components of sediment core PS1422-1. 14 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 547 records from RMT Trawl catch from the 2005/06 V3 BROKE-West voyage - Fish. 236 records from Rotifers of Macquarie Island. 160 records from Duck sightings per month, Macquarie Island. 408 records from Moss sampling in the Windmill Islands and the Vestfold Hills. 2 records from Mosquito Occurrence Dataset. 1636 records from Antarctic Echinoids: an interactive database. 444 records from ANTXXIII-8 Birds and Mammals. 63364 records from CCAMLR historic KRILL. 346 records from Antarctic Krill occurrence data from BAS expeditions. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 25 records from Antarctic Krill occurrence data from Spanish RV "Fruela". 3654 records from Antarctic Euphausiacea occurence data from "German Antarctic Marine Living Resources" (GAMLR) Expeditions. 44 records from Antarctic Euphausiacea occurrence data from ITALICA 2000 Expedition. 19 records from Antarctic Krill occurrence data from Japanese expeditions. 22 records from Antarctic Euphausiacea occurence data from Norwegian Antarctic Research Expedition 1976-77. 47 records from Antarctic Euphausiacea occurrence data from Norwegian Antarctic Research Expedition 1979. 86 records from Antarctic Euphausiacea occurence data from Polish FIBEX expeditions. 1268 records from Antarctic Krill occurrence data from US AMLR "US Antarctic Marine Living Resources" Program. 234 records from Antarctic Krill occurrence data from Australian expeditions. 6430 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 592 records from Antarctic Krill occurrence data from Ukraine YUGNIRO Institute. 2444 records from Collections data on ecology of bottom animal of the Southern ocean. 6014 records from globec/soglobec/process/krill. 516 records from Nemertina World Checklist. 41961 records from Tagged Seal Location Data from SOGLOBEC. 290 records from Bacteria and chlorophyll-a water column observations (surface to ~150m), April-August 2001, Continental Margin Western Antarctic Peninsula, GLOBEC. 6782 records from Zooplankton Abundance Based on Taxa and Life Stages or Size. 3974 records from Zooplankton abundance and population structures assessed during April-September of 2001-2, Southern Ocean, GLOBEC. 1150 records from Macrozooplankton concentrations estimated from MOCNESS tow samples, Continental Margin Western Antarctic Peninsula, GLOBEC. 2 records from Christopher Walker collection of Glomeromycotan fungi. 2777 records from Invertebrates compiled by W.Block. 74 records from (Appendix B) Coiling ratios of Globorotalia zealandica and Globorotalia praescitula plexi from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 856 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 808 records from (Table 2) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 113-690C on Maud Rise, Weddell Sea. 1356 records from (Table 1) Relative abundance of planktic foraminifera in Paleocene to Eocene sediments of ODP Hole 119-738C from the southern Kerguelen Plateau, Indian Ocean. 520 records from (Appendix C) Distribution of benthic foraminifera in surface sediments from the Chatham Rise. 316 records from Moss species from Heard Island, 1987 and 2000. 884 records from Invertebrate survey, Heard Island 2001. 98 records from Distribution of planktonic foraminifera in DSDP Hole 90-594 east of New Zealand. 4752 records from (Appendix B5) Distribution of planktic foraminifera in DSDP Site 90-594 east of New Zealand. 58 records from University of Alberta E. H. Strickland Entomological Museum (UASM). 1 records from LSUMZ (LSU MNS) Fishes Collection. 5492 records from Field Museum of Natural History (Botany) Bryophyte Collection. 60 records from (Table 7) Occurrence of selected diatom species in ODP Hole 119-744A. 98 records from Distribution of palynomorphs in Miocene sediments of ODP Site 188-1165 in the Prydz Bay, East Antarctica (Table 1). 43 records from Fundación Miguel Lillo - Colección Ornitológica. 4352 records from Seabird Atlas of South-eastern Australian Waters 1975-1993. 636 records from Distribution of surface phytoplankton between New Zealand and Antarctica, December 1957. 6 records from New species and phylogenetic relationships of the spider genus Coptoprepes using morphological and sequence data (Araneae: Anyphaenidae). 29520 records from (Table T2) Foraminifer distribution in ODP Site 188-1165 sediments. 757 records from Relative abundance of organic-walled dinoflagellate cysts in surface sediments. 797 records from (Table 3) Distribution of dinoflagellate cysts in Late Pliocene sediments of DSDP Hole 90-594 from Chatham Rise, Southwest Pacific. 990 records from Distribution of major planktic foraminifer at Site 177-1091. 985 records from Distribution of major planktic foraminifer at Site 177-1092. 770 records from Distribution of major planktic foraminifer at Site 177-1093. 246 records from Distribution of major planktic foraminifer at Site 177-1094. 1225 records from (Table T5) Benthic foraminifer occurrence in ODP Hole 183-1139A sediments. 451 records from Planktic foraminifera abundance of Hole 29-277. 53 records from Planktic foraminifera abundance of Hole 29-278. 8 records from Planktic foraminifera abundance of Hole 29-278A. 37 records from Planktic foraminifera abundance of Hole 29-279. 682 records from Planktic foraminifera abundance of Hole 29-279A. 415 records from Planktic foraminifera abundance of Hole 29-281. 53 records from Planktic foraminifera abundance of Hole 29-281A. 1347 records from (Table 16A) Occurrences of planktonic foraminifers in DSDP Hole 90-594, samples 594-1-CC through 594-30-CC. 1565 records from (Table 16B) Occurrences of planktonic foraminifers in DSDP Holes 90-594 and 90-594A. 3427 records from Occurrence of 13 crabeater seals (Lobodon carcinophaga) from ARGOS satellite track observations during campaign DRE1998. 104 records from Planktic foraminifera abundance of Hole 28-265. 59 records from Planktic foraminifera abundance of Hole 28-266. 2 records from Planktic foraminifera abundance of Hole 28-267. 1 records from Planktic foraminifera abundance of Hole 28-274. 1 records from New Zealand Coralline Algae. 39 records from Planktic foraminifera abundance of Hole 28-265. 1908 records from (Figure 3) Distribution of planktonic foraminifers in the Cenozoic sediments of DSDP Hole 71-511. 2945 records from (Figure 4) Distribution of planktonic foraminifers in the Cenozoic sediments of DSDP Site 71-512. 251 records from Planktic foraminifera abundance of Hole 71-513A. 18918 records from (Table 1) Distribution of benthic and planktonic foraminifers at DSDP Hole 28-270. 2 records from KUBI Ichthyology Collection. 213 records from Natural History Museum, University of Tartu. 354 records from Microfossil abundance of Hole 35-323. 48 records from Benthic foraminifera and algae abundance of Hole 35-325. 111 records from Planktic foraminifera abundance of Hole 36-329. 331 records from Range table from planktonic foraminifers in ODP Hole 141-859A. 84 records from Range table from planktonic foraminifers in ODP Hole 141-859B. 528 records from Range table from planktonic foraminifers in ODP Hole 141-860B. 58 records from Range table from planktonic foraminifers in ODP Hole 141-861A. 33 records from Range table from planktonic foraminifers in ODP Hole 141-861B. 529 records from Range table from planktonic foraminifers in ODP Hole 141-861C. 109 records from Range table from planktonic foraminifers in ODP Hole 141-861D. 54 records from Range table from planktonic foraminifers in ODP Hole 141-862A. 1 records from Range table from planktonic foraminifers in ODP Hole 141-862B. 4 records from Range table from planktonic foraminifers in ODP Hole 141-862C. 320 records from Range table from planktonic foraminifers in ODP Hole 141-863A. 172 records from Range table from planktonic foraminifers in ODP Hole 141-863B. 1084 records from University of British Columbia Herbarium (UBC) - Algae Collection. 3 records from MLZ Bird Collection (Arctos). 1 records from Herbarium of Umeå University (UME). 132 records from Field Museum of Natural History (Botany) Seed Plant Collection. 13 records from Colección Nacional de Entomología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 2 records from MBML-Herbario - Herbário Mello Leitão. 2 records from Range table from planktonic foraminifers in ODP Hole 178-1095A. 5 records from Range table from planktonic foraminifers in ODP Hole 178-1095B. 1 records from Range table from planktonic foraminifers in ODP Hole 178-1095D. 12 records from Range table from planktonic foraminifers in ODP Hole 178-1096A. 28 records from Range table from planktonic foraminifers in ODP Hole 178-1096B. 11 records from Range table from planktonic foraminifers in ODP Hole 178-1096C. 4 records from Range table from planktonic foraminifers in ODP Hole 178-1099A. 1 records from Range table from planktonic foraminifers in ODP Hole 178-1100C. 4 records from Range table from planktonic foraminifers in ODP Hole 178-1100D. 14 records from Range table from planktonic foraminifers in ODP Hole 178-1101A. 1 records from Range table from planktonic foraminifers in ODP Hole 178-1102C. 5 records from Range table from planktonic foraminifers in ODP Hole 178-1103A. 21 records from Range table from planktonic foraminifers in ODP Hole 183-1135A. 5 records from Range table from planktonic foraminifers in ODP Hole 183-1136A. 4 records from Range table from planktonic foraminifers in ODP Hole 183-1137A. 16 records from Range table from planktonic foraminifers in ODP Hole 183-1138A. 38 records from Range table from planktonic foraminifers in ODP Hole 183-1139A. 247 records from Occurence of foraminifera and other microfossils in sediment core CRP-2/2A (Table 1). 92 records from Siliceous microfossil occurrence, Site 177-1094. 290 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 2827 records from (Figure 5) Distribution of benthic foraminifers in the upper Eocene, Oligocene, and Quaternary of DSDP Hole 71-511. 5944 records from (Figure 6) Distribution of benthic foraminifers in middle-upper and Quaternary in DSDP Site 71-512. 4021 records from (Figure 7) Distribution of benthic foraminifers in the Oligocene to upper Miocene DSDP of Hole 71-513A. 3 records from Range table from benthic foraminifers in ODP Hole 178-1095A. 6 records from Range table from benthic foraminifers in ODP Hole 178-1095B. 3 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 14 records from Range table from benthic foraminifers in ODP Hole 178-1096C. 43 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 20 records from Range table from benthic foraminifers in ODP Hole 178-1099A. 26 records from Range table from benthic foraminifers in ODP Hole 178-1099B. 2 records from Range table from benthic foraminifers in ODP Hole 178-1100D. 14 records from Range table from benthic foraminifers in ODP Hole 178-1101A. 9 records from Range table from benthic foraminifers in ODP Hole 178-1103A. 12 records from Range table from benthic foraminifers in ODP Hole 181-1120B. 5 records from Range table from benthic foraminifers in ODP Hole 181-1120C. 56 records from Range table from benthic foraminifers in ODP Hole 181-1121B. 133 records from Range table from benthic foraminifers in ODP Hole 181-1122A. 206 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 1 records from Range table from benthic foraminifers in ODP Hole 188-1165A. 91 records from Range table from benthic foraminifers in ODP Hole 188-1165B. 8 records from Range table from benthic foraminifers in ODP Hole 188-1165C. 501 records from Range table from benthic foraminifers in ODP Hole 189-1169A. 881 records from Range table from benthic foraminifers in ODP Hole 189-1170A. 262 records from Range table from benthic foraminifers in ODP Hole 189-1170D. 124 records from Range table from benthic foraminifers in ODP Hole 189-1171A. 150 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 404 records from Range table from benthic foraminifers in ODP Hole 189-1171D. 1351 records from Colección Nacional de Herpetología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1349 records from Range table from benthic foraminifers in ODP Hole 141-861C. 211 records from Range table from benthic foraminifers in ODP Hole 141-861D. 9 records from (Tab. 9) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 36-330, Falcland Plateau. 208 records from Dinoflagellate cysts of ODP Hole 189-1171D. 1 records from Microfossil abundance of Hole 35-323. 116 records from Dinoflagellate abundance of Hole 71-511. 38 records from Dinoflagellate abundance of Hole 71-512. 9 records from Dinoflagellate abundance of Hole 71-513A. 5 records from Dinoflagellates, pollen and spore abundance of Hole 29-280A. 1 records from Dinoflagellates, pollen and spore abundance of Hole 29-281. 39 records from Dinoflagellate abundance of Hole 28-270. 88 records from Dinoflagellate abundance of Hole 28-274. 14 records from Microfossil abundance of Hole 29-277. 33 records from Microfossil abundance of Hole 29-278. 55 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1169A. 25 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1170A. 511 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1170D. 8 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1171A. 24 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1171C. 534 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1171D. 51 records from (Table III) Abundance of crustacea orders during RSS James Clark Ross cruise JR144. 18 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 141-860B. 39 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 141-861C. 8 records from CSIRO, Australian National Algae Culture Collection, Global, 1949-2008. 565 records from Marine palynomorph abundance estimates of sediment core CRP-2A (Fig. 2). 2443 records from Distribution of benthic foraminifera of sediment core PS1388-3. 79 records from (Table 3) Distribution of benthic foraminifera and radiolaria in DSDP Hole 90-594. 215 records from Colección de Mamíferos Marinos del Centro Nacional Patagónico. 1024 records from Benthic foraminiferal assemblages (living), surface data. 871 records from Benthic foraminiferal assemblages (dead), surface data. 152 records from Diversity of total live benthic foraminiferal assemblages in South Atlantic surface sediments. 306 records from Diversity of live benthic foraminiferal assemblages in South Atlantic surface sediments. 281 records from Diversity of dead benthic foraminiferal assemblages in South Atlantic surface sediments. 5955 records from Dead benthic foraminifera in South Atlantic surface sediments. 2306 records from (Table T4, T5, T6, T7) Percentage of agglutinated and calcareous benthic foraminiferal species in ODP Hole 178-1098C. 156 records from Relative abundance of deep-sea benthic foraminifera in surface sediments east of New Zealand. 1756 records from Relative abundances of middle Pleistocene benthic foraminifera in DSDP Site Site 90-594. 3210 records from Ice and animal observations during POLARSTERN cruise ANT-X/6. 11 records from Oberservation of birds at station PS14/142 along 49° West. 10 records from Oberservation of birds at station PS14/143 along 49° West. 11 records from Oberservation of birds at station PS14/145 along 49° West. 6 records from Oberservation of birds at station PS14/146 along 49° West. 7 records from Oberservation of birds at station PS14/148 along 49° West. 10 records from Oberservation of birds at station PS14/149 along 49° West. 6 records from Observation of birds at station PS14/151 along 49° West. 6 records from Observation of birds at station PS14/152 along 49° West. 3 records from Observation of birds at station PS14/153 along 49° West. 11 records from Observation of birds at station PS14/156 along 49° West. 10 records from Oberservation of birds at station PS14/157 along 49° West. 12 records from Oberservation of birds at station PS14/158 along 49° West. 15 records from Oberservation of birds at station PS14/159 along 49° West. 1 records from KUBI Invertebrate Zoology Collection. 10 records from R. L. McGregor Herbarium Vascular Plants Collection. 47 records from ANDEEP3: SeaStars (Echinodermata, Asteroidea). 24 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 293 records from EPOS3: SeaStars (Echinodermata, Asteroidea). 794 records from Walter Herwig 1978 (FFS): SeaStars (Echinodermata, Asteroidea). 13458 records from ABBBS Bird Banding records from the Australian Antarctic Territory and Heard Island.. 534 records from Leopard Seal census, Heard Island 1987/88. 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 11 records from Subantarctic Fur sealsat Heard Island, 1987/88. 70 records from Exotic terrestrial flatworms, Macquarie Island. 129 records from Squid specimens from the 1991/92 V6 AAMBER2 voyage. 1496 records from Senckenberg - CeDAMar Resource. 17 records from Texas A&M University Insect Collection. 2 records from UAZ Mammals. 3 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 12 records from Biological and palaeontological collection and observation data MNHNL. 740 records from Ifremer BIOCEAN database (Deep Sea Benthic Fauna). 1161 records from COMARGIS: Information System on Continental Margin Ecosystems. 31596 records from Biological observations from the Discovery Investigations 1925-1952. 3 records from Botany Division, Yale Peabody Museum. 846 records from Vertebrate Zoology Division - Ichthyology, Yale Peabody Museum. 10 records from Paleobotany Division, Yale Peabody Museum. 140 records from Bunger Hills, 1999/2000 survey - nest sites of snow petrels Pagodroma nivea. 140 records from Whale Observations from the British, Australian and New Zealand Antarctic Research Expedition (BANZARE) voyages 1929-30 and 1930-31. 5056 records from Nest census, Windmill Islands 2002/03. 165 records from Whale log - observations from ANARE voyages. 31209 records from BIOLOGICAL SCIENCES DATA. 218 records from KU Museum of Invertebrate Paleontology. 11 records from Collection Pisces SMF. 16 records from Collection Arachnology SMF. 522 records from Collection Porifera SMF. 181 records from Collection Mollusca SMF. 256 records from Collection Polychaeta SMF. 112 records from Collection Aves (spirit preserved) SMF. 260 records from Collection Cnidaria SMF. 1 records from Herbarium Senckenbergianum (FR). 3 records from Collection Aves (bird skeletons) SMF. 110 records from Collection Aves (bird skins) SMF. 84 records from Collection Crustacea SMF. 3327 records from Collection Bryozoa SMF. 8 records from Collection Foraminifera SMF. 1 records from Collection Pantopoda SMF. 4 records from Collection Tardigrada SMF. 3 records from SINGER Coordinator. 29 records from Hydroids of the BANZARE Antarctic expeditions 1929 - 1931. 156 records from Royal penguin Eudyptes schlegeli census and observations at North Head, Macquarie Island 1952/53. 302 records from Type Localities for organisms and fossils first described from Antarctica. 465 records from Fish catch from 1996/97 Voyage 2 WASTE (WOCE Antarctic Southern Transect Expedition). 829 records from Spring Phytoplankton Assemblages in the Southern Ocean Between Australia and Antarctica (CLIVAR-SR3). 121 records from Southern Giant Petrel census data within the Australian Antarctic Territory.. 607 records from King penguin census data, Gadget Gully, Macquarie Island (1993-2008). 5588 records from Snow Petrel nest census, Mawson region 2004/05. 306 records from Diatoms from SAZ Sediment traps. 897 records from Diatom and foraminiferal samples from surficial sediments of Prydz Bay, Antarctica. 685 records from Ohio State Acarology Laboratory (OSAL), Ohio State University. 40 records from Database of Native Plants in Taiwan. 140 records from AMNH Bird Collection. 82 records from AMNH Mammal Collections. 1 records from Bryophyte Collection - University of Washington Herbarium (WTU). 575 records from Mycological Collection - University of Washington Herbarium (WTU). 31 records from Lichen Collection - University of Washington Herbarium (WTU). 8 records from Occurence of marine palynomorphs of sediment core CRP-1 (Table 1). 59 records from Main components of radiolarian assemblage at Site 177-1092. 118 records from Siliceous microfossil occurrence, Site 177-1091. 131 records from Siliceous microfossil occurrence, Site 177-1092. 139 records from Siliceous microfossil occurrence, Site 177-1093. 98 records from Distribution of foraminifera, pre-Pliocene foraminifera and macrofossil debris in sediment core CRP-2 (Table 1). 69 records from Distribution of Miocene benthic foraminifera of sediment core CRP-1 (Fig. 1). 2002 records from Ophiuroidea collections of the Zoological Institute Russian Academy of Sciences. 6607 records from University of Florida Invertebrate Paleontology. 1 records from Entomological Collections (NHRS), Swedish Museum of Natural History (NRM). 1 records from (Table 1) King penguins' (Aptenodytes patagonicus) path characteristics to their colony, Kerguelen Island. 7 records from Deep sea Syllidae (Annelida, Phyllodocida) from Southwestern Atlantic. 1 records from SMNS Herpetologie. 79 records from MVZ Egg and Nest Collection (Arctos). 8063 records from (Appendix B1) Relative abundances of middle Eocene-late Oligocene calcareous nannofossils in ODP Hole 120-748B. 227 records from MNA (Section of Genoa) and NIWA Invertebrate Collection - Ross Sea Tanaidacea. 1165 records from Circumpolar dataset of sequenced specimens of Promachocrinus kerguelensis (Echinodermata, Crinoidea). 2 records from (Table 4) Differences in king penguin (Aptenodytes patagonicus) colony arrivals and departures based on age, Possession Island. 252 records from Colección Nacional de Ornitología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1 records from MAC - Herbário do Instituto do Meio Ambiente do Estado de Alagoas. 5420 records from Photodocumentation_of_Antarctic_Peninsula_Lichens. 3 records from Update of the genus Leptochiton (Mollusca: Polyplacophora) in Chilean deep waters: three new reports and description of two new species. 151 records from Naturalis Biodiversity Center (NL) - Porifera. 796 records from (Data S1) Palynology of IODP Hole 318-U1356A. 17 records from UPCB - Herbário do Departamento de Botânica. 765 records from Queensland Museum provider for OZCAM. 9 records from Bureau of Rural Sciences, Commercial Fisheries Presence, Australia, 2000-2002. 29 records from CM Birds Collection. 1 records from HURB - Herbário do Recôncavo da Bahia. 2 records from ArtenFinder. 169 records from (Table T2) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1171D sediments. 275 records from Lund Botanical Museum (LD). 579 records from Auckland Museum Land Vertebrates Collection. 338 records from Snow Entomological Museum Collection. 47 records from (Table 5) Vertical distribution of live benthic foraminifera in surface sediments at Bouvet Island stations. 39 records from Herbario CTES Plantas Vasculares. 18 records from (Table 1) Trawled distance, Isopoda per 1000 m haul length, expected number of species, evenness, and the Shannon-Wiener index during POLARSTERN cruise ANT-XXII/3 (ANDEEP III). 358 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of IODP Hole 318-U1356A. 86177 records from Geographically tagged INSDC sequences. 484 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 19 records from (Appendix B) Total cyst counts, and abundances of Selenopemphix undulata sp. nov. in Pacific Ocean surface samples. 86 records from Field Museum of Natural History (Botany) Lichen Collection. 4 records from HCDAL - Herbário Caririense Dárdano de Andrade-Lima. 10 records from TEPB - Herbário Graziela Barroso. 2 records from The Arthropoda Varia Collection at the Zoologische Staatssammlung München. 2 records from museu_paraense_emilio_goeldi-hexapoda_collection. 10 records from Field Museum of Natural History (Zoology) Fish Collection. 1365 records from MSB Mammal Collection (Arctos). 9 records from MSB Host Collection (Arctos). 9 records from Ghent university - Zoology Museum - Nematod Collection. 3 records from William Nylander lichen collection. 874 records from Geographic distribution of dinoflagellate cysts in surface sediments. 1 records from HST - Herbário Sérgio Tavares. 127 records from Coleccion Herpetologica Reptiles LJAMM-CNP. 39 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 55359 records from SAFRING: Historical Bird Ringing Records (2005-2009). 1361 records from The echinoderm collection (IE) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from R-Tipos - Herbário do Museu Nacional - Tipos. 267 records from The cnidarians collection (IK) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1659 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 32 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 6 records from Catálogo de los equinodermos recientes de México (Fase II). 11 records from (Table T6) Relative abundance of Cretaceous plant microfossil taxa of ODP Site 188-1166. 1 records from The Fish Database of Taiwan. 83 records from Animal Sound Archive. 1 records from Crustacea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1 records from SJRP-Algae - Herbário de algas de São José do Rio Preto. 3 records from Oregon State Ichthyology Collection. 97 records from Bernice P. Bishop Museum. 319 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD4. 33 records from The birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 19 records from Cowan Tetrapod Collection - Birds. 1089 records from Succession of benthic hard-bottom communities abundance at station Errina2012_IS_solar1. 44 records from Carnet en Ligne. 19 records from (Table T3) Calcareous nannofossil abundance of ODP Hole 189-1170A sediments. 90 records from Succession of benthic hard-bottom communities abundance at station Errina2012_IS_solar3. 106 records from East Weddell Sea echinoids from the JR275 expedition. 4 records from Description of a new hygrobatid genus from Chile (Acari, Hydrachnidia: Hygrobatidae). 19 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 60 records from (Table T1) Diatom biostratigraphy of ODP Hole 183-1140A. 185 records from Succession of benthic hard-bottom communities abundance at station Errina2012_AG. 279 records from UMMZ Birds Collection. 31 records from Australian National Insect Collection. 1 records from UFACPZ - Herbário da Universidade Federal do Acre. 437 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 431 records from Royal Botanic Garden Edinburgh Herbarium (E). 21 records from Colección de Entomología - Coleoptera. 1 records from tan-database. 12 records from Colección de Entomología - Hymenoptera - Aculeata. 5 records from Michigan State University Herbarium Vascular Plants. 105 records from Botany (UPS). 1 records from DMNH Birds. 288 records from Instituto de Ciencias Naturales. 6 records from (Figure 10) Occurrence of coccoliths in two carbonate cycles at DSDP Hole 71-511. 2 records from CNMT - Herbário Centro Norte Mato Grossense. 1 records from DMNS Egg Collection (Arctos). 4 records from ARC-PPRI: National Collection Of Fungi(1817-2009). 10 records from Mammalogy Collection - Royal Ontario Museum. 126 records from NMNH Paleobiology Specimen Records. 168375 records from Programa de Observadores a Bordo (POBCh) de la Secretaria de Pesca de la Provincia del Chubut, Argentina . Observer On board Program -Fisheries Secretariat of the Province of Chubut-Argentina (OOBPPCh). 1 records from crsn_data. 1 records from JPB - Herbário Lauro Pires Xavier. 1 records from Coleção Ictiológica (MNRJ), Museu Nacional (MN), Universidade Federal do Rio de Janeiro(UFRJ). 589 records from (Table 12) Distribution of benthic foraminifera in bottom sediments of the Lazarev Sea. 230 records from Colección de peces marinos del mar argentino y aguas adyacentes del INIDEP. 42 records from Colección de Entomología - Heteroptera. 1 records from R - Herbário do Museu Nacional. 116 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 12 records from (Table 1) Trawled distance, Isopoda per 1000 m haul length, expected number of species, evenness, and the Shannon-Wiener index during POLARSTERN cruise ANT-XIX/4 (ANDEEP II). 1 records from CAS Herpetology (HERP). 422 records from (Table T1) Planktonic and benthic foraminifer abundance of ODP Hole 183-1138A. 11 records from HUESB - Herbário da Universidade Estadual do Sudoeste da Bahia. 4 records from Ictiologia Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 3 records from Vascular plant herbarium, Tromsø Museum. 322 records from Queen Victoria Museum Art Gallery provider for OZCAM. 335 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1170D sediments. 74 records from (Table II) Abundance of epibenthic phyla and classes during RSS James Clark Ross cruise JR144. 7 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 6 records from Geothermal Fumarole Subsurface Mt. Erebus, Antarctica. 82 records from Vascular plant herbarium, NTNU University Museum. 1357 records from New Zealand Biodiversity Recording Network. 15 records from (Table 1) Mean body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 78 records from Observaciones de Especies Silvestres (by Charif Tala). 160 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 2 records from Colección de Entomología - Hymenoptera - Parasitica. 11591 records from (Table T6) Foraminifer distribution in ODP Hole 188-1167A sediments. 3 records from AUM Fish Collection. 295 records from Free-living marine Nematodes from San Antonio bay (Río Negro, Argentine) 2009.. 2 records from NCSM Invertebrates Collection. 2601 records from UB - Herbário da Universidade de Brasília. 22 records from Naturalis Biodiversity Center (NL) - Mollusca. 563 records from The crustaceans collection (IU) of the Muséum national d'Histoire naturelle (MNHN - Paris). 7 records from PEUFR - Herbário Professor Vasconcelos Sobrinho. 2 records from ConDidact Citizen Science Surveys - Spiders 2014. 1715 records from (Table 2) Live benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 148 records from KUBI Herpetology Collection. 10067 records from Australian Museum provider for OZCAM. 16 records from (Table 1) Diving behaviour of male Adélie penguins (Pygoscelis adeliae) with and without corticosterone implants at Pointe Géologie. 2 records from Colección de Entomología - Orthoptera. 1 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 911 records from Registros de hongos en áreas protegidas de la Argentina. 17474 records from Allan Herbarium (CHR). 9 records from IRAI - Herbário do Parque da Ciência Newton Freire Maia. 46 records from NOAA Deep Sea Corals Research and Technology Program. 19 records from Entomology at ZMUC, Natural History Musem of Denmark. 94 records from (Appendix 4) Calcareous nannofossils in ODP Hole 113-689B. 7 records from HPL - Herbário do Jardim Botânico Plantarum. 226 records from SIO Marine Vertebrate Collection. 70539 records from Neptune Deep-Sea Microfossil Occurrence Database. 907 records from VERTEBRADOS DE VALOR ESPECIAL EN ÁREAS PROTEGIDAS DE LA ARGENTINA. 2333 records from Auckland Museum NZ Marine Collection. 9 records from CEN - Herbário da Embrapa Recursos Genéticos e Biotecnologia. 160 records from MVZ Bird Collection (Arctos). 316 records from Vascular Plant Herbarium, Oslo (O). 30 records from (Table 2) Benthic isopod species of the Ross Sea, their bathymetry and distribution in the Southern Ocean. 218 records from Occurrences in SinBIOTA. 84 records from (Table T4) Abundance of foraminifers and presence of other fragments in ODP Hole 188-1166A sediments. 22 records from (Table 1) Distribution of upper Campanian-lower Maestrichtian calcareous nannofossils at DSDP Hole 71-511. 32 records from Succession of benthic hard-bottom communities abundance at station Errina2012_CS. 161 records from KUBI Ornithology Collection. 1 records from tan-database. 1371 records from Lichen herbarium, Tromsø Museum. 1 records from Herbario de Briófitos de la Universidad de Salamanca: SALA-Bryo. 34 records from E. C. Smith Herbarium (ACAD). 485 records from Colección de referencia de otolitos, Instituto de Ciencias del Mar-CSIC. 1 records from NCSM Mammals Collection. 12 records from (Table IV) Abundance of isopoda families during RSS James Clark Ross cruise JR144. 91 records from Moss herbarium, UiB. 878 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 90 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 68 records from UF FLMNH Ichthyology. 2440 records from Auckland Museum Marine Collection. 39 records from (Table T3) Calcareous nannofossil abundance of ODP Hole 189-1171A sediments. 1 records from The Pisces Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 86 records from BHCB-SL - Herbário UFMG - Samambaias e Licófitas. 1390 records from (Appendix 1) Calcareous nannofossils in ODP Hole 119-738B. 5050 records from New Zealand Fungal and Plant Disease Collection (PDD). 10 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Paleopalynology National Collection (BAPal).. 3 records from EAN - Herbário Jaime Coelho de Moraes. 141 records from (Table T3) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1138A. 3 records from The Coleoptera collection (EC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 40 records from (Table T1) Kerogen and organic constituents in ODP Hole 183-1138A, Kerguelen Plateau. 1906 records from Marine Invertebrate from Argentina, Uruguay and Chile. 38 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 16370 records from Records from the NIWA AllSeaBio marine biology database. 89 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 1006 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 709 records from Invertebrates (Type Specimens) of the Swedish Museum of Natural History. 4 records from SP-Bryophyta - Maria Eneyda P. Kauffman Fidalgo. 21 records from Fundación Miguel Lillo - Colección Criptogámica. 3 records from SysTax - Herbaria. 3514 records from Protected species bycatch in New Zealand fisheries. 594 records from Geneva Herbarium – General Collection (G). 6730 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 11889 records from Instituto de Botánica Darwinion. 9 records from Opiliones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 594 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 24 records from UFMT - Herbário UFMT. 426 records from South Australian Museum Australia provider for OZCAM. 677 records from Lichen herbarium, UiB. 2 records from Colección de Entomología - Coleoptera - Chrysomeloidea. 2059 records from (Table 22) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-594. 15 records from HEPH - Herbário Ezechias Paulo Heringer. 2 records from HRCB - Herbário Rioclarense. 10 records from PACA-AGP - Herbarium Anchieta. 13 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 3 records from UESC - Herbário Universidade Estadual de Santa Cruz. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences